Abnormal dynamic brain activity and functional connectivity of primary motor cortex in blepharospasm. (6th January 2022) - Luo, Yuhan; Guo, Yaomin; Zhong, Linchang; Liu, Ying; Dang, Chao; Wang, Ying; Zeng, Jinsheng; Zhang, Weixi; Peng, Kangqiang; Liu, Gang
Abstract: Background and purpose: Accumulating evidence indicates that dynamic amplitude of low‐frequency fluctuations (dALFF) or dynamic functional connectivity (dFC) can provide complementary information, distinct from static amplitude of low‐frequency fluctuations (sALFF) or static functional connectivity (sFC), in detecting brain functional abnormalities in brain diseases. We aimed to examine whether dALFF and dFC can offer valuable information for the detection of functional brain abnormalities in patients with blepharospasm. Methods: We collected resting‐state functional magnetic resonance imaging data from 46 patients each of blepharospasm, hemifacial spasm (HFS), and healthy controls (HCs). We examined intergroup differences in sALFF and dALFF to investigate abnormal regional brain activity in patients with blepharospasm. Based on the dALFF results, we conducted seed‐based sFC and dFC analyses to identify static and dynamic connectivity changes in brain networks centered on areas showing abnormal temporal variability of local brain activity in patients with blepharospasm. Results: Compared with HCs, patients with blepharospasm displayed different brain functional change patterns characterized by increased sALFF in the left primary motor cortex (PMC) but increased dALFF variance in the right PMC. However, differences were not found between patients with HFS and HCs. Additionally, patients with blepharospasm exhibited decreased dFC strength, but no change in sFC, between right PMC and ipsilateral cerebellum compared with HCs; these findings were replicated when patients with blepharospasm were compared to those with HFS. Conclusions: Our findings highlight that dALFF and dFC are complementary to sALFF and sFC and can provide valuable information for detecting brain functional abnormalities in blepharospasm. Blepharospasm may be a network disorder involving the cortico‐ponto‐cerebello‐thalamo‐cortical circuit. Abstract : Patients with blepharospasm exhibited increased dynamic amplitude of low‐frequency fluctuations in the right primary motor cortex (a) and decreased dynamic functional connectivity strength between the right primary motor cortex and ipsilateral cerebellum (b) compared with healthy controls. Blepharospasm may be a network disorder involving the cerebello‐cortical circuits.